Counseling on the Use of Media in Flood Disaster Mitigation in Bulukerto Village, Batu City - Mondry, Mondry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
The occurrence of a flash flood in Batu City caused local residents to flock to apply for coordination with the Batu City BPBD. This coordination is aimed at carrying out flood prevention programs, including disaster mitigation education for local residents. The output we are targeting is community outreach with speakers or speakers who are experts in their respective fields. The hope of this service program is that it can increase the role of Brawijaya University in implementing the Tri Dharma of Higher Education. Apart from that, it is also hoped that the community service program will be the best opportunity to strengthen the capacity of the Bulukerto Village community as a community that is aware and resilient to flood disasters, as well as building the modalities of the Bulukerto Village community in having the ability to be empowered in the field of disaster mitigation and utilizing the media.